Parametric Study of Nonplanar Dust Acoustic Solitons in Two‐Dimensional Superthermal Dusty Plasmas. Issue 10 (11th July 2016) - Khan, S.; Ata‐ur‐Rahman,; Ali, S.; Khalid, M.; Khattak, N. A. D.; Zeb, A.
Abstract: The nonlinear properties of two dimensional low‐frequency electrostatic excitations of charged dust particles (or defects) are studied in a collisionless, unmagnetized dusty plasma. A fully ionized three‐component model plasma consisting of kappa distributed electrons, Maxwellian ions, and negatively charged massive dust grains is considered. In this regard, the well known reductive perturbation technique is used to the hydrodynamical equations and the Poisson equation, obtaining the cylindrical Kadomtsev–Petviashvili (CKP) equation. A parametric investigation indicates that the structural characteristics of these nonlinear excitations (width, amplitude) are significantly affected by the plasma nonthermality as well as by the relevant plasma parameters, such as dust concentration and dust temperature. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)